Healthy food, unhealthy food: Indigenous perspectives on the nutrition transition - Maria Amalia Pesantes; Mariella Bazán Macera; Sabine Mercier; Pamela Giselle Katic (Taylor & Francis Group, 2024)
ABSTRACTAmazonian Indigenous Peoples are undergoing drastic changes in their ways of life including the quality and availability of food and its impact on their health and well-being. Indigenous populations have their own perspectives and interpretations of dietary changes unfolding in their communities. Based on in-depth interviews, observations and validation workshops we explored the way Awajún describe and problematise the concept of healthy and unhealthy food in the context of the nutrition transition. We learn that the characteristics of 'good food' are informed by their capacity to give strength, protect health and enable them to be hardworking people. On the contrary, food that comes from the city weakens the body and may result in health problems. For the Awajún, chicken with hormones, fish preserved in cans, and powdered milk negatively affect their health. We argue that the dichotomy 'healthy' and 'unhealthy' used to classify food provides information not only about Indigenous conceptualisations of health and die, but is also a critique of broader structural processes affecting their well-being. The terms, explanations and idioms used by the Awajún to talk about food, provide an insight into Indigenous perspectives and knowledge key to informing global health interventions in culturally appropriate ways.